Revealing Gen Z’s Interest in Sharia Investment in The Capital Market - Nurul Syafika; Eka Sri Wahyuni; Kustin Hartini (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: This study investigates the influence of financial literacy, income, and technology on Generation Z's interest in investing in the Islamic capital market. The research addresses the growing importance of understanding the factors that encourage young individuals to participate in sharia-compliant investments, aiming to support the development of the Islamic financial market in Indonesia. Methods: The study employed a quantitative research method, collecting data through questionnaires distributed to 60 respondents using a saturated sampling technique. The data were analyzed to determine the relationship between the variables and Generation Z's investment interest. Results: The findings reveal that financial literacy and access to technology significantly affect Generation Z's interest in Islamic investments, while income has a relatively minor influence. These results highlight the critical role of knowledge and technology in shaping investment behavior among young individuals. Conclusion and suggestion: To attract more young investors to the Islamic capital market, efforts should focus on enhancing financial literacy through targeted education and providing accessible, user-friendly technological tools. This study contributes to the literature by examining the unique context of Islamic investment among Indonesia's younger generation and offers actionable insights for financial institutions, policymakers, and educators to foster sharia-compliant investment practices.